The Effect of Leadership Style, Work Motivation, Work Stress and Employee Diversity on Employee Turnover with Employee Satisfaction as a Mediating variable in Mining Companies in Morowali, Sulawesi Tengah - Pratama, Ryan; Yuniwinarsih, Daning; Arman, Marcella Devara (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study was to analyze leadership style, employee motivation, work stress, employee diversity on employee turnover with employee satisfaction as a mediating variable. This research was conducted at mining companies in the Morowali area, Central Sulawesi, research is needed in order to determine the equality of treatment carried out through the variables mentioned above. This research was analyzed with a quantitative method approach where the analysis used was descriptive statistics and hypothesis testing with partial least square (PLS). This research uses the explanatory research method. Sample determination is done by simple random sampling method. Our research sampling was conducted in 4 different companies so that in each company we took a sample of 21 people. The results showed that there is a significant effect of employee diversity on job satisfaction where the existence of employee diversity in increasing employee job satisfaction has a moderate/moderate effect at the structural level. Then there is a significant effect of employee job satisfaction on employee turnover where the existence of employee job satisfaction in increasing employee turnover has a low influence at the structural level.